2016
DOI: 10.1002/pro.2943
|View full text |Cite
|
Sign up to set email alerts
|

The MTA1 subunit of the nucleosome remodeling and deacetylase complex can recruit two copies of RBBP4/7

Abstract: The nucleosome remodeling and deacetylase (NuRD) complex remodels the genome in the context of both gene transcription and DNA damage repair. It is essential for normal development and is distributed across multiple tissues in organisms ranging from mammals to nematode worms. In common with other chromatin-remodeling complexes, however, its molecular mechanism of action is not well understood and only limited structural information is available to show how the complex is assembled. As a step towards understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 30 publications
3
54
0
Order By: Relevance
“…Therefore, from this set of experiments it cannot be concluded that two RBBPs directly interact. In fact, we and others have demonstrated that MTA1 can simultaneously bind two molecules of RBBP4/7 [18, 19], indicating that the apparent RBBP-RBBP interaction is likely to be indirect – mediated by MTA1/2/3. We have observed a similar phenomenon when probing for other interactions between pairs of subunits, including CHD4 and RBBP7 (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, from this set of experiments it cannot be concluded that two RBBPs directly interact. In fact, we and others have demonstrated that MTA1 can simultaneously bind two molecules of RBBP4/7 [18, 19], indicating that the apparent RBBP-RBBP interaction is likely to be indirect – mediated by MTA1/2/3. We have observed a similar phenomenon when probing for other interactions between pairs of subunits, including CHD4 and RBBP7 (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…4C shows pulldowns using the same proteins co-expressed in HEK293 cells. Using the RRL system, RBBP4 interacts with MTA2 (consistent with [17][18][19]) but not with GATAD2B, MBD3cc or the HDAC1 + MTA2N complex. In contrast, and in line with the previous section, RBBP4 appeared to interact with every subunit tested in the HEK293 pulldowns.…”
Section: An Improved Nurd Subunit Interaction Map Derived From In Vitmentioning
confidence: 86%
See 3 more Smart Citations